Bioaktivitas Isolate Katekin Dari Ekstrak Gambir (Uncaria gambir) - Nova Lusiana; Eva Agustina; Risa Purnamasari (Program Studi Biologi, Fakultas Sains dan Teknologi, Universitas Islam Negeri Sunan Ampel Surabaya, 2025)
Gambier leaves (Uncaria gambir) are a primary source of bioactive compounds, particularly catechins, which have high potential for therapeutic applications due to their antioxidant activity. This study aims to investigate the isolation process of catechins from gambier leaves, determine the catechin content, and evaluate the antioxidant activity of the isolated compound. The research methodology includes maceration of gambier leaves using 96% ethanol as a solvent, isolation using chromatography, catechin content analysis using HPLC, and antioxidant activity assessment using the DPPH (2,2-diphenyl-1-picrylhydrazyl) method. The results indicate that catechin isolates were successfully obtained from gambier leaves through chromatographic separation. Optimal separation was achieved using an N-hexane:ethyl acetate (2:1) mobile phase. The catechin content in the gambier leaf isolate was 129.99 ppm, while the antioxidant activity test showed an IC50 value of 25.2 ppm, indicating very strong antioxidant activity. Catechins from gambier leaves have great potential as a natural antioxidant source due to their high free radical scavenging activity.